LIFE STRESS AND PSYCHOLOGICAL FACTORS IN FUNCTIONAL DYSPEPSIA - Tobón, Sergio; Vinaccia Alpi, Stefano; Sandín, Bonifacio (Anales de Psicología / Annals of Psychology, 2003)
The aim of this paper was to present a critical analysis of non-ulcer or functional dyspepsia (FD) and its relationship to life stress and psychological factors. The implications of these factors are reviewed with emphasis on the multifactorial nature of the FD. The selected review suggests that life events, anxiety, anxiety disorders, depression, some psychopathological symptoms, somatization, and personality traits (neuroticism and concealed hostility) are associated with FD, being some of these variables able to differentiate FD from other functional gastrointestinal disorders. We highlight the possible relationship between these factors and the hypothesized pathophysiological mechanisms, as well as their implications for psychological therapy.